An Unusual Presentationof Herpes Simplex Virus Type 1Infection in a Child - Hale Sakallı; Hilal Erinanc; Recep Dursun; Esra Baskin (Karger Publishers, 2013)
We describe an 11-year-old girl presenting with lichen simplex chronicus (LSC) and acute bilateral carpal tunnel syndrome (CTS) following herpes simplex virus type 1 (HSV-1) infection as evidenced by serological data and by detection of HSV-1 DNA in the blood with the use of PCR. Based on the literature search, this case represents the first childhood case of LSC and acute bilateral CTS following HSV-1 infection. The experience with this patient emphasizes the importance of serological tests and PCR as well as the other laboratory techniques for the accurate diagnosis and management of the disease.